2014
DOI: 10.1063/1.4895769
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical vector beams of light from an electrically excited plasmonic lens

Abstract: International audienceThe production of cylindrical vector beams from a low-energy, electric, microscale light source is demonstrated both experimentally and theoretically. This is achieved by combining a “plasmonic lens” with the ability to locally and electrically excite propagating surface plasmons on gold films. The plasmonic lens consists of concentric circular subwavelength slits that are etched in a thick gold film. The local excitation arises from the inelastic tunneling of electrons from the tip of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…The coherent sum of all these dipole fields generates optical fringes in the Fourier plane. This experiment, which is reminiscent of Young's double slit experiments, allows us to exploit the coherence of SPPs in order to tailor focussed beam such as Bessel modes or polarized vortices [65,66]. Like for LRM the Fourier plane is insensitive to an index mismatch between the oil and the objective microscope glass.…”
Section: Surface Plasmon Polariton Scatteringmentioning
confidence: 99%
“…The coherent sum of all these dipole fields generates optical fringes in the Fourier plane. This experiment, which is reminiscent of Young's double slit experiments, allows us to exploit the coherence of SPPs in order to tailor focussed beam such as Bessel modes or polarized vortices [65,66]. Like for LRM the Fourier plane is insensitive to an index mismatch between the oil and the objective microscope glass.…”
Section: Surface Plasmon Polariton Scatteringmentioning
confidence: 99%
“…2(b)]. This very low angular divergence as well as beaming of light along the optical axis is obtained because the scattered light is emitted in phase from the five slits of the plasmonic lens [10]. This occurs when the period of the circular grating (i.e., the radial distance between two nearest slits) equals an integral number of SPP wavelengths.…”
Section: A Full-spectrum Angular Emission Patternsmentioning
confidence: 97%
“…Intensity profiles taken from the Fourier images are shown below each image in a polar plot. For these images, light is collected using an objective lens of NA = 1.45 and the image resolution is 0.027k 0 per pixel (i.e., the NA = 1.5 circle has a diameter of ≈108 pixels) and the acquisition time is 300 s. slits gives rise to the emission of a cylindrical vector beam of light with radial polarization [10]. Figure 2(a) shows the resulting Fourier-space optical image for a five-slit circular grating of period 700 nm and inner diameter 5 μm.…”
Section: A Full-spectrum Angular Emission Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that the gap mode can also excite the surface plasmon polaritons (SPPs) propagating along the metal surface 31,32 . This provides an efficient, local, electrical way of launching SPPs in optical structures, and its applications received considerable attention recently [33][34][35][36][37][38] . These results suggest that the electrical excited gap plasmon modes have several optical decay channels.…”
Section: Introductionmentioning
confidence: 99%